Education, gender and cross-cultural experience with reference to elite Arab women - Kirdar, S; Serra Kirdar (2004)
﻿ The core of the thesis investigates the role of education in the engendering of cultural change and leadership among a select group of a powerful 'first generation' of Arab women; specifically, the role of dual educational/cultural experiences, both Arab and Western. The broader aim of the study is to analyze the merging of cultural traditionalism and modernity and how dual education has enhanced the ability of women, especially Arab women, to become leaders in their professional careers, and within their respective communities, whilst still maintaining strong ties to their culture, religion and traditions, albeit to varying degrees. The writer has chosen to investigate the association between cultural identity and educational experience of elite educated Arab women, through a small sample, who have had exposure to both Western and Arab educational systems at different points in their lives. The researcher's heritage has led to a fundamental ideological interest in the coexistence of traditionalism and modernisation and whether the two can complement one another. There are now a significant number of Arab women who have had the privilege of education and exposure to the two types of systems. Yet, gender constraints and predefined gender roles still very much dictate the socio-cultural contexts in which such women have to operate. The patriarchal 'system' is omnipresent in the West as well as in the Arab world. The challenges the writer has faced even as a 'Western' Arab to reconcile tradition and intellectual and educational exposure has served as a greater impetus for this investigation. The investigation and the intent of this thesis as described above, is to test the preliminary hypothesis that, in the context of elite Arab women, their exposure to both West and Arab educational cultures is germane to their potential for influencing female professional development. How their educational experiences have influenced their own identities and their ability to adhere to the gender roles prescribed is of significant interest. What influence has such education had on these women's prospects for instituting and pioneering change in their respective societies and professions? Is the synergy of certain aspects of modernity and tradition possible? The general conclusion is that it is.